TRADISI â€œMBEGEGEK UGAK-UGEKâ€ KHATAMAN QURâ€™AN MASYARAKAT DISEKITAR GOA SELOMANGKLENG TULUNGAGUNG JAWA TIMUR - Purwasih, Galuh Dwi (SAMAWAT: Journal Of Hadith and Qur’anic Studies, 2023)
This paper seeks to express cultural reasoning in the â€œMbegegek Ugak-Ugekâ€ Khatam Qurâ€™an tradition around Selomangkleng Cave. In addition, this paper also reveals the meaning of this tradition for the people of Selomangkleng Cave. Data collection techniques are based on observation, in-depth interviews and review of secondary data. The results of this study found that the Mbegek Ugak-Ugek tradition in the Khatam Quran around the Selomangkleng cave is one of the traditions that expresses Semar's behavior in religious puppet stories. For the people around the Selomangkleng cave, the Mbegegek Ugak-Ugek tradition in the Khatam Quran is an initiation process of greatness and a form of gratitude for God's majesty. A form of stability and solemnity towards Allah according to the word reflected in the Koran. The Mbegegek Ugak-Ugek tradition "in Khatam Quran has the meaning of caring in social relations between people, especially in building togetherness and mutual cooperation between intimate relatives and the community. Keywords: Meaning, Tradition and Khataman Qur'an